OEDIPUS-KOMPLEKS PADA TOKOH MA KUN DALAM NOVEL TOKYO TAW?: OKAN TO BOKU, TOKIDOKI, OTON KARYA RIRI FURANKI - Putu, Linda Trinayanti Putrawan (Humanis, 2015)
This research titled " Oedipus - complex of figure Ma kun in the novel Tokyo Tawa : Okan to Boku , Tokidoki , Oton” taken from Riri Furanki. This reseach analyzed the characteristics of oedipus-complex, factors that cause oedipus-coplex, and the effort of figure Ma kun to overcome oedipus-complex. This reseach used a descriptive method of analysis and informal method. The theory used in this research is literary of psychology theory supported by psychosexual development theory taken from Sigmund Freud.The results show that the characteristics of oedipus - complex experienced by Ma kun, such as: 1) Ma kun loves his mother as he loves his girl friend; 2) ) he is always dependent on his mother ; and 3 ) the jealousy of his father and another man close to his mother.Causes of the oedipus complex on Ma kun because of his past experiences , such as : 1 ) the separation of both parents ; 2 ) a tenuous relationship between father and son ; and 3 ) he is spoiled a lot by his mother. Ma kuns efforts to overcome oedipus complex , such as : 1 ) attempting to stay apart from his mother ; and 2 ) seeking to establish a relationship with the opposite sex .
Keywords: Literary of Psychology , psychosexual development , the Oedipus – complex